Desmoplastic Infantile Ganglioglioma/Astrocytoma (DIG/DIA) Are Distinct Entities with Frequent BRAFV600 Mutations - Wang, Anthony C. (Mol Cancer Res, 2018)
Desmoplastic infantile ganglioglioma (DIG) and desmoplastic infantile astrocytoma (DIA) are extremely rare tumors that typically arise in infancy; however, these entities have not been well characterized in terms of genetic alterations or clinical outcomes. Here, through a multi-institutional collaboration, the largest cohort of DIG/DIA to date is examined using advanced laboratory and data processing techniques. Targeted DNA exome sequencing and DNA methylation profiling were performed on tumor specimens obtained from different patients (n = 8) diagnosed histologically as DIG/DIGA. Two of these cases clustered with other tumor entities, and were excluded from analysis. The remaining 16 cases were confirmed to be DIG/DIA by histology and by DNA methylation profiling. Somatic BRAF gene mutations were discovered in 7 instances (43.8%); 4 were BRAF(V600E) mutations, and 3 were BRAF(V600D) mutations. Three instances of malignant transformation were found, and sequencing of the recurrence demonstrated a new TP53 mutation in one case, new ATRX deletion in one case, and in the third case, the original tumor harbored an EML4–ALK fusion, also present at recurrence. DIG/DIA are distinct pathologic entities that frequently harbor BRAF(V600) mutations. Complete surgical resection is the ideal treatment, and overall prognosis is excellent. While, the small sample size and incomplete surgical records limit a definitive conclusion about the risk of tumor recurrence, the risk appears quite low. In rare cases with wild-type BRAF, malignant progression can be observed, frequently with the acquisition of other genetic alterations. IMPLICATIONS: DIG/DIA are a distinct molecular entity, with a subset frequently harboring either BRAF(V600E) or BRAF(V600D) mutations.